Genetic Connectivity in a Cooperatively Breeding Carnivore Between Two Protected Areas - Ariana L. Cerreta; Jennifer R. Adams; Bridget L. Borg; Mathew S. Sorum; Lisette P. Waits; David E. Ausband (Ecology and Evolution)
ABSTRACT Wildlife populations are increasingly threatened by human activities. Most studies, however, are often short in duration or do not encompass the large spatial extent necessary to measure the potential effects of human activities on population vital rates. Furthermore, the life history features of species with high fecundity and excellent dispersal capabilities can act as buffers against the potential negative effects of human activities on their populations. We used a 30‐year dataset of genetic samples from gray wolves (Canis lupus) in Alaska, USA, to examine genetic connectivity and diversity between National Park units separated by a region with recurrent human‐caused mortality. We found that the two protected populations were genetically similar and that dispersal events occurred between them even though they are > 450 km apart. We posit that intact ecosystems and a history of continuous distribution of wolves surrounding the affected regions likely maintained the genetic connectivity of wolves in the two protected areas.